Adaptation and validation of Malay six-item cognitive impairment test in screening for cognitive impairment among elderly outpatients in Hospital Tengku Ampuan Afzan - Idris, Umi Kalsom Mohd (2017)
The usage of a valid and reliable tool is crucial in order to improve the detection of cognitive impairments among elderly patients in hospital settings. Six-Item Cognitive Impairment Test (6-CIT) a potential screening tool because it is concise, fast, and easy to administer verbally. It has excellent sensitivity, specificity, and correlates well with the Mini-Mental State Examination (MMSE). To date, the instrument‟s adaptability and performance have yet established upon the local population. This study aimed to validate the Malay version of 6-CIT as well as determining its psychometric properties, and correlation with the gold standard as a screening tool for cognitive impairment in Malay speaking elderly outpatients in local hospital settings. This cross-sectional study conducted between August to November 2016 at the Orthopaedics and Medical Outpatient Clinics Hospital Tengku Ampuan Afzan. The study divided into two phases and the sampling method done by a convenient sampling. Phase 1 involved translation process of instrument and pilot study upon 24 Malay speaking elderly. Two hundred and thirty four Malay speaking aged 60 and above elderly, who was not involved in Phase 1 study, not deaf, and not too ill approached for Phase 2. The data then analysed for descriptive, exploratory and confirmatory factor analyses, the standard measures of diagnostic test at two cut-offs (7/8 and 10/11) and analysis of correlations compared to gold standard. From the factor analyses, orientation and attention-memory with goodinternal consistency (Cronbach's alpha = 0.819 and 0.708) extracted. The overall performance of the Malay 6-CIT was excellent. At two cut-offs (7/8 and 10/11) the sensitivity were 95%, while the specificity ranged from 85% to 97% compared to MMSE-M. When compared to Elderly Cognitive Assessment Questionnaire (ECAQ Malay), the sensitivity = 100% and specificity = 84%. Significant negative correlation between total and each factor of the Malay 6-CIT with gold standard obtained. In conclusion, the translation process of this tool was easy. The administration was quick and favorable in busy settings. Orientation and attention-memory model concluded from the factor analyses proved to be valid and reliable in detecting cognitive impairment, consistent with previous studies. The results of the present research provide evidence for the Malay 6-CIT used as an alternative screening instrument for cognitive impairment in future.